2022
DOI: 10.1186/s41235-022-00372-y
|View full text |Cite
|
Sign up to set email alerts
|

Interpolated testing and content pretesting as interventions to reduce task-unrelated thoughts during a video lecture

Matthew S. Welhaf,
Natalie E. Phillips,
Bridget A. Smeekens
et al.

Abstract: Considerable research has examined the prevalence and apparent consequences of task-unrelated thoughts (TUTs) in both laboratory and authentic educational settings. Few studies, however, have explored methods to reduce TUTs during learning; those few studies tested small samples or used unvalidated TUT assessments. The present experimental study attempted to conceptually replicate or extend previous findings of interpolated testing and pretesting effects on TUT and learning. In a study of 195 U.S. undergraduat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 77 publications
(209 reference statements)
0
9
0
Order By: Relevance
“…The overall prevalence and within-task increase in rates of mind-wandering have several implications for applied settings where attentional lapses lead to consequential errors (e.g., mind-wandering in air traffic, military, or medical contexts). Although several studies in the present meta-analysis examined mind-wandering in contexts relevant to real-world outcomes (e.g., mind-wandering during lectures in an educational context; Dhindsa et al, 2019; Kane et al, 2017; Martin et al, 2018; Welhaf et al, 2022), future research might focus more directly on examining mind-wandering during well-controlled but ecologically valid tasks and activities. Mind-wandering has been successfully assessed in a range of ecologically valid laboratory-based tasks (Konu et al, 2021) and during naturalistic, real-world activities (Killingsworth & Gilbert, 2010; Mckeown et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence and within-task increase in rates of mind-wandering have several implications for applied settings where attentional lapses lead to consequential errors (e.g., mind-wandering in air traffic, military, or medical contexts). Although several studies in the present meta-analysis examined mind-wandering in contexts relevant to real-world outcomes (e.g., mind-wandering during lectures in an educational context; Dhindsa et al, 2019; Kane et al, 2017; Martin et al, 2018; Welhaf et al, 2022), future research might focus more directly on examining mind-wandering during well-controlled but ecologically valid tasks and activities. Mind-wandering has been successfully assessed in a range of ecologically valid laboratory-based tasks (Konu et al, 2021) and during naturalistic, real-world activities (Killingsworth & Gilbert, 2010; Mckeown et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several experiments from my laboratory revealed that interpolated testing, where participants are given periodic quizzes during a lecture regarding specific contents can reduce mind wandering and boost memory for lecture content compared with restudying the same information (Jing et al, 2016; Szpunar et al, 2013). Using slightly different materials and procedures, Welhaf et al (2022) also observed that interpolated testing reduced mind wandering during a video-recorded lecture (albeit with a relatively small effect size), but failed to observe a significant benefit of interpolated testing on memory for lecture content. As noted by Welhaf et al (2022), one potentially important difference between their methods and those used by Jing et al (2016) and Szpunar et al (2013) is that in the latter studies, participants were allowed to take notes during the lecture, whereas in Welhaf et al (2022), participants were not allowed to take notes.…”
Section: Absentmindednessmentioning
confidence: 96%
“…Using slightly different materials and procedures, Welhaf et al (2022) also observed that interpolated testing reduced mind wandering during a video-recorded lecture (albeit with a relatively small effect size), but failed to observe a significant benefit of interpolated testing on memory for lecture content. As noted by Welhaf et al (2022), one potentially important difference between their methods and those used by Jing et al (2016) and Szpunar et al (2013) is that in the latter studies, participants were allowed to take notes during the lecture, whereas in Welhaf et al (2022), participants were not allowed to take notes. Interpolated testing was associated with increased note-taking in two experiments by Szpunar et al (2013) and in Experiment 1 but not Experiment 2 by Jing et al (2016).…”
Section: Absentmindednessmentioning
confidence: 96%
“…Thus, interpolated testing appears able to produce both backward (i.e., testing enhances long-term retention) and forward (i.e., testing enhances new learning) testing effects (e.g., Szpunar et al, 2008;Yang et al, 2018Yang et al, , 2021. Subsequent research on interpolated testing has typically found at least some form of learning benefit, but not always (Haagsman et al, 2020;Jing et al, 2016;Lavigne & Risko, 2018;Szpunar et al, 2014;van der Meij & Böckmann, 2021;Welhaf et al, 2022).…”
Section: Interpolated Testingmentioning
confidence: 99%
“…For example, in the original Szpunar et al (2013) investigation, they demonstrated that individuals in the interpolated test condition reported mind wandering less and took more notes than those in the other conditions. However, those effects have been less consistent (Jing et al, 2016;Szpunar et al, 2014;Welhaf et al, 2022). Szpunar et al (2013) also found that individuals in their interpolated test condition reported that the experience of learning the lecture material was less "mentally taxing," led to less anxiety about an upcoming test, and produced less negative affect than individuals in their restudy and nontested group.…”
Section: Interpolated Testingmentioning
confidence: 99%